An innovative full-size pathogenic tandem duplication mutation precise detection system based on next-generation sequencing - Li-Li Zhang; Zhe Wang; Ying Zhou; Dai-Yang Li; Xiao-Nian Tu; Yu-Xia Li; Ke-Ming Du; Zhong-Zheng Zheng (Experimental Biology and Medicine)
Accurate identifying internal tandem duplication (ITD) mutation is indispensable for diagnosis and prognosis of acute myeloid leukemia (AML) patients, but specialized full-size detection tools are lacking. Therefore, we aimed to develop a reliable system for accurate assessment of ITD mutations of various size ranges and improve prognosis for AML. Bone marrow samples from AML patients from December 2021 to March 2022 were collected for methodology establishment. After a large-scale sample testing by next-generation sequencing (NGS), a short-read tandem duplication recognition system based on soft-clip was established. During performance validation, the lower detection limit was set to a parameter close to capillary electrophoresis (“gold standard”) by adjusting reference values (sensitivity 3–5%). Data simulation was performed using the FLT3 gene CDS as wild-type data. Methodological concordance of this system with capillary electrophoresis was analyzed. The applicability to other pathogenic tandem duplication mutations was validated. We have developed an innovative NGS-based system named “ITDFinder” for accurate detection of ITD mutations, with the lower detection limit of 4%, corresponding to a sequencing depth of 1000X. Compared to capillary electrophoresis, ITDFinder exhibited good consistency (mean difference: −0.0085) in mutation detection and correlation across various length of ITD. Clinical case validation (n = 1,032) showed an overall agreement rate of 96.5% between the two approaches used for characterization. In addition, data simulation results suggested that the new system could observe BCOR-ITD and KMT2A-PTD mutations (depths, 500–1300X; mutation rates, 0.04–0.8). The innovative mutation detection system is appropriate to small-to large-sized ITDs and other pathogenic tandem duplication mutations, expected to save 96.3% of the workload. This offers significant potential for accurate clinical assessment of ITD mutations and subsequent prognosis in AML patients.